2000
DOI: 10.3354/meps194203
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Cd, Cr and Zn from zooplankton prey to mudskipper Periophthalmus cantonensis and glassy Ambassis urotaenia fishes

Abstract: Assimilation efficiency (AE) of metals from ingested food is critical for understanding trace metal accumulat~on and trophic transfer in aquatic animals. Most recent measurements of metal AEs have been on aquatic invertebrates, whereas relatively few studes have examined metal assimilation in fishes. In this study we determined the AEs of Cd, Cr and Znin 2 fishes (pelagic glassy Ambassis urotaenia, Ambassidae, and the intertidal mudskipper Penophthalmus cantonensis, Gobiidae) feeding on 2 zooplankton prey (bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
59
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 21 publications
7
59
1
Order By: Relevance
“…These generally consume their prey whole, and may be contaminated by organs (gills, bones, liver, spleen, etc) that specifically accumulate metals (see for example Wood andVan Vleet, 1996, andParsons, 1999). None of the metals analyzed in the present study has been reported as being commonly bioaccumulated (e.g., Miramand et al, 1998; but see Ni et al, 2000) and, in fishes, metal levels generally diminish from the bottom (i.e., mullet, as primary consumers) to the top of the food chain (i.e., snook, as secondary consumers) (Mance, 1987). Our study showed little evidence for such phenomena (T ables 2 and 4) or its opposite (i.e., bioaccumulation).…”
Section: Discussionmentioning
confidence: 56%
“…These generally consume their prey whole, and may be contaminated by organs (gills, bones, liver, spleen, etc) that specifically accumulate metals (see for example Wood andVan Vleet, 1996, andParsons, 1999). None of the metals analyzed in the present study has been reported as being commonly bioaccumulated (e.g., Miramand et al, 1998; but see Ni et al, 2000) and, in fishes, metal levels generally diminish from the bottom (i.e., mullet, as primary consumers) to the top of the food chain (i.e., snook, as secondary consumers) (Mance, 1987). Our study showed little evidence for such phenomena (T ables 2 and 4) or its opposite (i.e., bioaccumulation).…”
Section: Discussionmentioning
confidence: 56%
“…Among the many elements studied so far, the AE of MeHg and radiocesium in fishes are the highest (Ni et al 2000, Zhao et al 2001, Baines et al 2002. For example, the AE of radiocesium range between 78 and 95% in the marine mangrove snappers Lutjanus argentimaculatus (Zhao et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that the AEs of elements in fish were directly correlated with the metal distribution in the nonexoskeleton fraction of the copepod prey. The correlation was based on a variety of elements with contrasting physiological and geochemical behaviors, but it was not observed in the two fish Periophthalmus cantonensis and Ambassis urotaenia (Ni et al 2000). Recently, Wallace and Luoma (2003) introduced the concept of trophically available metal (TAM) (combination of organelles, HDP, and HSP) and indicated that about 100% of the TAM could be assimilated by predators.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that different prey resulted in a variation of metal AEs in fish (Ni et al 2000;Xu and Wang 2002), suggesting that different forms of metals in the food may influence the availability of metals. Some previous studies have indicated that the cytosolic distribution of metals in marine phytoplankton is important in dietary assimilation by marine herbivores (Reinfelder and Fisher 1991;Wang and Fisher 1996;Chong and Wang 2000), but assimilation in marine predators appears to be more complicated.…”
mentioning
confidence: 99%